2008
DOI: 10.1080/13685530801953994
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of testosterone administration on symptoms of the lower urinary tract in men with late-onset hypogonadism: A pilot study

Abstract: Testosterone administration improved symptoms of LUTS in men with late-onset hypogonadism. The mechanism of action is as yet not understood, but it may be connected with or parallel with the effects of testosterone on penile tissues in hypogonadal men, such as on nitric oxide and phosphodiesterase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 30 publications
5
38
1
1
Order By: Relevance
“…However, some prospective (Kristal et al 2008, Trifiro et al 2010 and cross-sectional studies (Schatzl et al 2000, Tan et al 2003, Roberts et al 2004, Miwa et al 2008, St Sauver et al 2011 have demonstrated an inverse association between serum testosterone and LUTS or BPH. Consistent with these observations, testosterone replacement therapy has been reported to relieve LUTS in hypogonadal men with both BPH (Holmäng et al 1993, Saad et al 2007, Kalinchenko et al 2008, Karazindiyanoglu & Ç ayan 2008, Amano et al 2010, Shigehara et al 2011 and MetS (Haider et al 2009).…”
Section: Introductionsupporting
confidence: 62%
“…However, some prospective (Kristal et al 2008, Trifiro et al 2010 and cross-sectional studies (Schatzl et al 2000, Tan et al 2003, Roberts et al 2004, Miwa et al 2008, St Sauver et al 2011 have demonstrated an inverse association between serum testosterone and LUTS or BPH. Consistent with these observations, testosterone replacement therapy has been reported to relieve LUTS in hypogonadal men with both BPH (Holmäng et al 1993, Saad et al 2007, Kalinchenko et al 2008, Karazindiyanoglu & Ç ayan 2008, Amano et al 2010, Shigehara et al 2011 and MetS (Haider et al 2009).…”
Section: Introductionsupporting
confidence: 62%
“…Nitric oxide (NO) is also one of the mediators of dilatation of the bladder neck and urethra (McVary 2006) by its smooth muscle relaxing effect in the urogenital system (Pradidarcheep 2008). It was suggested that TRT could improve the urinary symptoms by increasing NO production by modulatory effect on NO synthase (Chamness et al 1995) or phosphodiesterase which might be linked to TRT effect on the penile tissues in hypogonadal men (Kalinchenko et al 2008). In addition, as increased rho-kinase activity coincides with the development of LUTS in elderly men, therefore TRT-induced inhibition of rho-kinase is thought to decrease smooth muscle cell proliferation and to decrease adrenergic contractions (Rees et al 2003).…”
Section: Discussionmentioning
confidence: 96%
“…However, it is not known whether these beneficial effects of TRT can be continued in the long term (Yassin et al 2014). Moreover, the significance of low T as well as the exact mechanism of TRT-induced improvement of LUTS are not well-understood (Kalinchenko et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…When comparing with the previous treatment period consisting of intramuscular injections of T cypionate 200-300 mg over 8 weeks, the quality-of-life surveys for the patients treated with the T gel showed a trend toward greater physical and emotional wellbeing and cognitive function (mean increase: 10%). T-gel therapy in 88 HIV-positive men with abdominal obesity and low T was associated with greater decrease in whole body, total and subcutaneous abdominal fat mass and a greater increase in lean mass compared with placebo [121]. Beneficial effects of topical T gel were also observed in patients with end-stage liver disease [122].…”
Section: Additional Potential Therapeutic Uses Of Testosterone Gelsmentioning
confidence: 95%